Актуальні питання відшкодування майнової шкоди реабілітованому - Наумова, А. О.; Naymova, A. O.; ORCID: http://orcid.org/0000-0002-4273-8068 (Юридичний науковий електронний журнал. - 2022. - № 4. - С. 169-172, 2022)
У статті висвітлено проблемні питання пов’язані із відшкодуванням шкоди реабілітованій особі в кримінальному процесуальному праві. Проаналізовано юридичну літературу, нормативно-правові акти України та визначено поняття та складові майнової шкоди. Досліджено кримінально-процесуальне законодавство держав СНД та визначено, що на законодавчому рівні питання відшкодування шкоди, завданої невинуватій у вчинені злочину особі, розглядається по-різному. Запропоновано доповнення в чинний КПК України.

The article highlights the problematic issues related to compensation for the rehabilitation of a rehabilitated person in criminal procedure law. The legal literature, normative legal acts of Ukraine are analyzed and the concepts and components of property damage are determined. The criminal procedure legislation of the CIS states has been studied and it has been established that at the legislative level the issue of compensation for damage caused by a crime to an innocent person is considered differently. It is proposed to supplement the current Criminal Procedure Code of Ukraine with the chapter “Rehabilitation”, in which the article “Compensation for property damage to the rehabilitated” should be worded as follows: “1. Property damage caused to a person by illegal and unjustified criminal prosecution, illegal detention, illegal application of a preventive measure in the form of detention or a written undertaking not to leave, illegal conviction, includes real damage, lost profits and is subject to full recovery. compensation. state. 2. A rehabilitated person is entitled to compensation: 1) real losses that are reimbursed in cash: wages, earnings, pension, scholarship, cash social assistance, cash, which were recognized as material evidence; the value of things and other property seized or converted into state revenue; costs that are determined by the sentence and charged to the person; a fine imposed by a court; legal aid costs; funds withheld from the salary of an illegally convicted person to the state revenue; Other expenses; 2) real damages reimbursed in kind: property recovered from the innocent in favor of other individuals or legal entities; objects, things, valuables that are seized as material evidence and are not destroyed, not damaged; property that was confiscated and not transferred to state revenue; 3) lost profits, which are unearned products, fruits, income and everything that is produced, obtained, obtained from the thing or brings the thing; unearned income in the form of dividends from equity securities, derivative securities, other financial or commodity resources; unearned income from entrepreneurial activity, which the person could not realize due to illegal detention, illegal conviction; unearned income from winnings on bonds, lotteries, etc.; 3. The amount of real losses, lost profits, physical damage, which are subject to compensation to the rehabilitated, is determined in accordance with the requirements of the Civil Code of Ukraine”.

В статье отражены проблемные вопросы, связанные с возмещением вреда реабилитированному лицу в уголовном процессуальном праве. Проанализирована юридическая литература, нормативно-правовые акты Украины и определены понятия и составляющие имущественного вреда. Исследовано уголовно-процессуальное законодательство государств СНГ и определено, что на законодательном уровне вопрос возмещения вреда, причиненного невиновному в совершении преступления лицу, рассматривается по-разному. Предложено дополнение в действующий УПК Украины.
Current issues of compensation of property damage to the rehabilitated
Наумова, А. О. Актуальні питання відшкодування майнової шкоди реабілітованому [Електронний ресурс] / Наумова А. О. // Юридичний науковий електронний журнал. - 2022. - № 4. - С. 169-172. - Режим доступу: http://lsej.org.ua/4_2022/37.pdf.
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Цивільне право. Civil Law. Гражданское право; майнова шкода; property damage; имущественный вред; відшкодування майнової шкоди; compensation for property damage; возмещение имущественного вреда; реабілітований; rehabilitated; реабилитированный; зарубіжний досвід; foreign experience; зарубежный опыт; законодавство; legislation; законодательство